New Reference State Model of the Third-Order PWL Dynamical Systems - J. Horska; Z. Kolka; J. Brzobohaty; J. Pospisil (Radioengineering, 2000)
Starting from the first elementary canonical state model, the newsimple state model of the third-order dynamical systems that belong toClass C is derived. A typical property of this new model is a verysimple form of its partial transformation matrix in the conditions oflinear topological conjugacy, which represents the unity matrix.Complete state equations and the corresponding integrator-based blockdiagram of this model are shown and relation to the first canonicalform is graphically illustrated.